The performance of chitosan/gelatin composite microspheres in the wash‐off procedure of reactive dyeing. (13th July 2016) - He, Baoyuan; Wang, Xuechuan; Xue, Haiyan
Abstract : A chitosan/gelatin composite microsphere (CGMS) adsorbent prepared by inverse suspension was used as a reactive dye washing agent. Techniques such as scanning electron microscopy, X‐ray diffraction analysis, and atomic force microscopy facilitated the evaluation of the materials. A series of experiments were conducted to assess the effect of variables, i.e. initial pH, temperature, microsphere dosage, and contact time. The wash‐off effectiveness increased with increase in temperature and decrease in pH. Results obtained from this study showed that it was possible to reduce the number of wash‐off stages and the water consumption. Furthermore, the microspheres had the properties of resistance to hard water and electrolyte as a wash‐off agent. The efficiency of the microspheres can rival routine detergent in colour fastness, while the chemical oxygen demand of the wash‐off residue of the microspheres amounted to about 1/10 of the chemical oxygen demand of detergent wash‐off residue. This research proved that chitosan/gelatin composite microspheres are a potential candidate for use as an adsorbent washing agent for reactive dyes.